Dengue Infection and Its Relationship with Evans Syndrome: A Pediatric Case - Ivan Jose Ardila Gomez; Pilar Pérez López; Mónika Rocío Hernández Carreño; Juan Camilo Barrios Torres (Case Reports in Medicine)
Dengue is a single-stranded RNA virus belonging to the Flaviviridae family. It is an endemic virus in tropical countries. In Colombia, 4 serotypes are present, and the disease is a burden for public health, social programs, and the economic sectors. The main vector is Aedes aegypti, and most infections are asymptomatic or minimally symptomatic. The hemorrhagic appearances of severe dengue are due to plasma leakage as a result of increased vascular permeability, severe thrombopenia, and hemoconcentration. In 2020, 78,979 cases of dengue were reported in Colombia. 38,836 (49.2%) of them were warning-free signs, 39,246 (49.7%) with warning signs, and 897 (1.1%) of severe dengue. As it is well-known, viral diseases are immune system activators, triggering off a loss of tolerance in it. Dengue is not an exception, and it is able to explain different autoimmune phenomena including macrophage activation. Mechanisms have been described by which an exacerbated response of the disease is triggered through the increase of infected cells, formation of immune complexes, and complement pathway activation, which lead to a cross-reaction of viral antigens with epithelial cells with platelets with subsequent endothelial dysfunction and bleeds. The first description of Evans syndrome was made in 1951 by Robert Evans. This syndrome is characterized by the combination of autoimmune hemolytic anemia, immune thrombocytopenia, and, less common/usual, immune neutropenia. This disease’s etiology is unknown, and the dysregulation of the immune system is among its possibilities. Here, we present the case of an unusual hematological and immunological complication of a patient who developed Evans syndrome during severe dengue, taking into account the concomitantly limited literature available for these two diseases, the need for a broader diagnostic approach, multidisciplinary intervention, and a more complex therapeutic approach.